Addressing palliative care and end-of-life issues in patients with advanced cancer: a systematic review of communication interventions for physicians not specialised in palliative care - Corinna Bergelt; Karin Oechsle; Nele Harnischfeger; Hilke M Rath (BMJ Open)
Objective To identify and summarise evaluated interventions aiming to improve the communication of palliative care (PC) and end-of-life (EoL) issues in physicians caring for cancer patients. Such interventions are needed with regard to the aim of an earlier communication of those issues in oncology daily practice, which is associated with a range of benefits for patients and caregivers but is often impeded by physicians’ communication insecurities.Design Systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources Relevant publications were systematically searched in MEDLINE, PsycINFO, CINAHL and Web of Science databases in September 2020 with an update in July 2021.Eligibility criteria We included publications reporting a quantitative evaluation of a communication intervention on one or more PC/EoL issues with a communication-related main outcome. Target group had to be physicians caring for cancer patients non-specialist in PC.Data extraction and synthesis Two independent raters extracted intervention characteristics, publication characteristics and publication quality. Results were narratively synthesised.Results 24 publications reporting 22 interventions were included. 13 publications reported randomised controlled trials. A majority of the interventions addressed one specific PC/EoL issue, most often breaking bad news. Teaching strategies mostly involved role-plays. Target group were mainly oncologists. In addition to self-reported outcome measurements for evaluation, most publications also reported the use of external rating data. All but one publication reported significant intervention effects on at least one outcome parameter. Publication quality was overall moderate.Conclusions The empirically tested communication interventions on PC/EoL issues seem to effectively improve physicians’ communication. Future interventions should focus on other issues than breaking bad news, such as preparing for the future. Target group should also be organ-specific oncologists, as all primary caring physicians are responsible for timely communication. Our risk-of-bias assessment revealed some weaknesses, indicating that more high-quality studies for evaluation are needed.PROSPERO registration number CRD42020191054.